Fish Behavioral Responses to External Stimuli and Fishing Method Research - Chen, Shuai; Li, Lingzhi; Li, Shuai; Zhao, Guoqing; Shen, Fengyuan (International Journal of Natural Resources and Environmental Studies, 2025)
Fish behavioral responses to external stimuli serve as a critical basis for designing and optimizing fishing methods, directly impacting catch efficiency, resource assessment, and fisheries management. Since the 1950s, international academic circles have advanced this field through major conferences (e.g., Hamburg 1957, London 1963) and systematic research, notably led by the United States, Russia, Japan, and Norway. China has published works such as Fish Behavior and Fishing Technology and Fish Ethology since the 1980s, achieving significant progress in phototaxis, acoustic-electrical stimulation, and feeding behavior. Research has progressively expanded into interdisciplinary applications including aquaculture, ecological conservation, and bionics. Fish responses to external stimuli (light, sound, electromagnetic fields, water currents, etc.) vary by species. For instance, the sixline wrasse exhibits extreme sensitivity to water currents, the American whitefish detects ultrasonic waves to warn of predators, and Japanese eels rely on geomagnetic navigation for spawning. Building on these behavioral traits, fisheries have developed multiple behavioral control technologies: reducing bycatch through net-based isolation barriers, guiding migratory fish away from hydroelectric turbine units using underwater strobes, protecting dolphins from gillnet entanglement via ultrasonic devices, and employing phototaxis and electric field effects for light-based trapping and electrofishing techniques. However, existing technologies still face challenges, such as isolation devices affecting trawl efficiency and fish developing adaptations to persistent stimuli. Future research should focus on understanding fish perception mechanisms (e.g., auditory sensitivity and directional orientation), optimizing stimulus signal types and sustainability, and deepening fundamental studies on behavioral memory to advance the precision and ecological friendliness of fishing methods.